TITIK KRITIS PRODUKSI MINYAK SAWIT BERKELANJUTAN DI PT.XYZ - Winda Adelita Saragih; Bayu Krisnamurthi; Netti Tinaprilla (Forum Agribisnis, 2017)
The change of business paradigm towards sustainable development requires industry players to produce palm oil in a sustainable manner. One of them is to follow the guidelines of Principles and Criteria (PnC) of sustainable palm oil production endorsed by Roundtable on Sustainable Palm Oil (RSPO). Researchers interested to know the constraints (critical point) of the company in meeting all the principles and criteria for sustainable palm oil production. Identification of critical points will have an important role to know how far the performance and constraints faced by the company in fulfilling all the principles and criteria to produce sustainable palm oil. The purpose of this study is to analyze the critical point on sustainability criteria and indicators in PT.XYZ. Methods of data collection research conducted by interview and observation in the field. Researchers use RSPO Principles and Criteria (PnC) parameters as parameters of sustainable palm oil production implementation. Method of data analysis using FMECA (Failure Modes, Effects and Criticality Analysis ) method with 2 stages, namely FMEA (Failure Mode and Effects Analysis) and CA (Criticality Analisis). The FMECA analysis shows that there are 5 critical criteria and 6 critical indicators in fulfilling all the principles and criteria of sustainable palm oil production in PT.XYZ.